2019
DOI: 10.1155/2019/4197164
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Attract Endothelial Progenitor Cells via a Positive Feedback Loop between CXCR2 and CXCR4

Abstract: Mesenchymal stem cells (MSCs) can attract host endothelial progenitor cells (EPCs) to promote vascularization in tissue-engineered constructs (TECs). Nevertheless, the underlying mechanism remains vague. This study is aimed at investigating the roles of CXCR2 and CXCR4 in the EPC migration towards MSCs. In vitro, Transwell assays were performed to evaluate the migration of EPCs towards MSCs. Antagonists and shRNAs targeting CXCR2, CXCR4, and JAK/STAT3 were applied for the signaling blockade. Western blot and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In addition to the IL‐6/JAK/STAT3 pathway, the activation of EGFR, fibroblast growth factor receptor, C‐X‐C chemokine receptor (CXCR), G‐protein coupled receptor, and B7‐H3, as well as the stimulation with carcinogenic (areca nut extract) and others, can also cause STAT3 phosphorylation via the JAK/STAT3 pathway. 69 , 70 , 71 , 72 , 73 It was reported that other classes of non‐receptor PTKs could stimulate STAT3 activation. The Src family of kinases, including Src, Lck, Hck, Lyn, Fyn, and Fgr can mediate STAT3 activation.…”
Section: Regulators Of the Stat3 Pathwaymentioning
confidence: 99%
“…In addition to the IL‐6/JAK/STAT3 pathway, the activation of EGFR, fibroblast growth factor receptor, C‐X‐C chemokine receptor (CXCR), G‐protein coupled receptor, and B7‐H3, as well as the stimulation with carcinogenic (areca nut extract) and others, can also cause STAT3 phosphorylation via the JAK/STAT3 pathway. 69 , 70 , 71 , 72 , 73 It was reported that other classes of non‐receptor PTKs could stimulate STAT3 activation. The Src family of kinases, including Src, Lck, Hck, Lyn, Fyn, and Fgr can mediate STAT3 activation.…”
Section: Regulators Of the Stat3 Pathwaymentioning
confidence: 99%
“…Meanwhile, the secretion of FGF-1 and FGF-2 was found to be escalated post-ES on the fibroblasts [55]. It is important to note that FGF-1, FGF-2, and VEGF are angiogenesis factors [63,64], which must be present for effective wound healing. In another study on HUVEC and HMEC, ES increased the migration speed of both cells to the cathode, and the mitosis cleavage plane for both cells was found to be perpendicular to the field vector compared to the random orientation in control on top of the increased production of chemokine receptors CXCR4 and CXCR2 [60], which are crucial for endothelial cell migration [65].…”
Section: Proliferative Phasementioning
confidence: 99%
“…As a precursor of ECs, EPCs also differentiate into ECs and promote ischemia angiogenesis through their paracrine function ( 91 , 92 ). MSCs could attract and promote the migration and vascularization of EPCs, which may depend on a positive feedback loop between CXCR-2 and CXCR-4 ( 93 , 94 ). The viability and ability of MSCs to promote nerve regeneration is also improved by EPCs through PDGF-BB/PDGFR-β signaling ( 95 ).…”
Section: Interactions Among Mscs and Ecs Epcs And Pericytesmentioning
confidence: 99%